Effects of water content change path on laboratory and field compaction of lime stabilized expansive soil - Guo, Yugeng; Zhang, Fuhai; Liu, Zhengrong; Meng, Qingxiang (Frontiers in Earth Science, 2023)
Generally, the soil requires to be compacted in highway construction. The expansive soil is a special type of soil that is highly susceptible to variations in water content, which affects the degree of compaction at the same compaction energy. In the present study, a series of wet compaction tests and dry compaction tests were carried out in the laboratory. Laboratory test results show that dry compaction will produce a higher optimum water content and a higher maximum dry unit weight compared to wet compaction, because its matric suction is smaller. Field compaction tests were also conducted, the results showed that there might be a risk of under-compacting soils during construction caused by different water content change path in actual field conditions.